The functions of constitutional monarchy in Malaysian political system: The perceptions of Malay community - Dzulkifli, Fatimah Zainab; Mohd Zameri, Nasrul Dadziruddin (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
The monarchy plays a vital role in Malaysia’s political system whether it is at federal or state level. Its formal duties are stated within the Malaysian constitution. It is a continuity to promote political and ruling stability. Hence Malaysia practises a system of government based on the Constitutional Monarchy and Parliamentary Democracy. The objectives of this paper are to study the extent of the monarchy roles as stated in the constitution. In addition, it is also to evaluate the perception of the Malay community towards the relationship between the monarchy and the government as well as the constitutional monarchy and the general community. The study limits its focus only to the role of monarchy in Malaysia and will also discuss about the additional roles of the monarchy besides its formal roles. The study will focus more on library research. Data are obtained through printed materials produced by local and international writers and publishers. The Malaysian Constitution will be the primary reference to the study. The perceptions of the Malay community are obtained through observations and reading materials that represents a part, if not the whole, of Malay’s perception towards the issue. Through this study, it can be summarised that the Malaysian Constitution bestows special privileges to the monarchy system. Thus, the boundary listed in the constitution ensures that the monarchy system continues to be revered. Loyalty to the King becomes a tradition and custom to the Malay community.